Pengembangan E-Learning Berbasis Android pada SMK Bahrul Maghfirah sebagai Media Pembelajaran Online - Dewi, Novi Ayu Kristiana; Aprianto, Aprianto; Ibnuwati, Sri; Utami?, Bernadhita Herindri Samodera (Attractive : Innovative Education Journal, 2022)
The purpose of the article was to create an online learning application-based android at SMK Bahrul Maghfirah as a learning media due to a covid-19 pandemic. Data collection methods consisted of observation, interviews, and literature study. While the application development method used the waterfall method, which was the method used to develop software. The waterfall method in this study consists of needs analysis, design, design implementation using a programming language that can be translated by a computer, application testing using the black box method, and application maintenance. Based on the test results, it was known that the android-based e-learning application can run according to its function, hence it was expected to be applied as an online learning media at SMK Bahrul Magfirah. Keywords: E-Learning Based Android, Learning Media, Development Online Learning